Skip to main content
1 of 2

Translating a complex predicate into predicate logic

i have a silly logic question again. How would you translate the following sentence into predicate logic?

No dolphin sings unless it jumps.

My guess is that it is an E-sentence of the form "no A is B", where A stands for "dolphin" and the predicate B stands for "is such that it sings unless it jumps". But how can we analyze B? It seems that the predicate B has the form "p unless q" which can be symbolized as "∼q → p". That's why the predicate has the can be analyzed as "∼Fx → Gx", with "Fx" meaning "x jumps" and "Gx" meaning "x sings". This leads to the symbolization:

∼∃x (Kx ∧ (∼Fx → Gx))

But this is incorrect! The correct solution is the following:

∼∃x (Kx ∧ ∼(Gx → Fx))

What am I doing wrong? I'm a bit confused in figuring out the structure of the predicate. Thanks for your help again!